2018
DOI: 10.1002/masy.201800130
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Characterization of Melt Electrospun Fibers and Films Based on PLA‐PHB Blends: Diffusion, Drug Release, and Structural Features

Abstract: Comparative structural‐dynamic characterization of the biopolyester blends based on poly(3‐hydroxybutyrate) and poly‐L‐lactide (PLA) [PHB/PLA] is performed. The melt electrospun fibers and molded films with the same compositions (1/0, 1/9, 3/7) but obtained by two different fabrication ways are explored by combination of structural and dynamic methods. The structural‐dynamic features such as segmental mobility (by spin‐probe ESR technique), thermophysical transitions (by DSC), and surface morphology (by SEM) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
(53 reference statements)
1
3
0
Order By: Relevance
“…Hence, higher accessibility of amorphous areas to ozone should occur. As shown before for the fibrillar and plane film composites of PHB-PLA [55], in the range of component ratio 30:70-70:30, their crystallinity was decreased, which reflected an enhancement in segmental dynamics-namely, at those polymer ratios, the time correlation values have a flat minimum (see Figure 4 in [47]). Besides, in this PHB concentration interval, the diffusivity of the low-molecular-weight compound-in particular, the modeling drug, dipyridamole-was increased, which elucidated the mechanism of controlled release in PHB-PLA electrospun fibers [37].…”
Section: Ozone Oxidationsupporting
confidence: 64%
“…Hence, higher accessibility of amorphous areas to ozone should occur. As shown before for the fibrillar and plane film composites of PHB-PLA [55], in the range of component ratio 30:70-70:30, their crystallinity was decreased, which reflected an enhancement in segmental dynamics-namely, at those polymer ratios, the time correlation values have a flat minimum (see Figure 4 in [47]). Besides, in this PHB concentration interval, the diffusivity of the low-molecular-weight compound-in particular, the modeling drug, dipyridamole-was increased, which elucidated the mechanism of controlled release in PHB-PLA electrospun fibers [37].…”
Section: Ozone Oxidationsupporting
confidence: 64%
“…Recently, Liu, Cao, Iordanskii et al [33] have reported the production and characterization of PHA-PHB spun fibers produced by melt electrospinning. In the following paper of the same authors [34], the comparison of melt electrospun PHB-PLA fibers and molded films with analogous compositions has been presented to elucidate the diffusivity impact on drug release features. In addition to the usage of electrospun fibers in biomedicine as well as at development of innovative packaging materials, they are starting to be actively used for the development of innovative absorbents for pollutants removing [35].…”
Section: Introductionmentioning
confidence: 99%
“…The latter process, therefore, opens up the incorporation thermolabile substances into electrospun biopolymer films, including natural extracts, for the development of active packaging systems [7,72,110]. In this new trend, PHB has begun to have a greater impact, both individually and with polymer mixtures such as PLA, polyanilines, or lignins [64,101,108,[111][112][113]. In particular, the combination of PLA and PHB biopolyesters, since both are bio-based thermoplastic polyesters, results very promising for packaging and other short-term applications [64,101].…”
Section: Processing Aspects Of Phb-based Formulationsmentioning
confidence: 99%